Aplikasi Pupuk Organik Cair Menggunakan Bioaktivator Mikroorganisme Indigenous HPPB Untuk Pertumbuhan Desmodium heterophyllum pada Tanah Bekas Tambang Batu Kapur PT. Semen Padang - Rizqa Zidna Chairafahmi; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2018)
The research about application of liquid organic fertilizers with indigenous microorganism bioactivator of HPPB for growth of Desmodium heterophyllum on limestone mined land at PT. Semen Padang, had been conducted from May to August 2015 in Nursery and Reforestation, Laboratory of Plant Physiology Department of Biology, and the Laboratory of Soil Science Faculty of Agriculture, Andalas University, Padang. The research aimed to determine the effect and concentration of Liquid Organic Fertilizers (LOF) by using indigenous microorganism bioactivator originated from HPPB in limestone mined land ofPT. Semen Padang. This study used Completely Randomized Design (CRD) with five treatments and four replications. The treatments were control without LOF (A), 10% LOF (B), 20% LOF (C), 30% LOF (D) and 40% LOF (E). The results showed that 10% LOF was the best concentration to increase the number of leaves (36,44), percentage of land cover (6,71%) and fresh weight of plants (5,15g).